Investigaciones cualitativas en salud pública publicadas en revistas biomédicas colombianas entre el 2011 y el 2021. - Rodríguez-Gómez, Rodolfo (Biomédica: Revista del Instituto Nacional de Salud, 2023)
Introduction: Qualitative research seeks to understand the meaning and perspective of individuals and investigates considering the context. This paradigm allows the interpretation and study of phenomena from their own complexity. In public health, qualitative research has gained ground, as it allows the study of subjective aspects of the health-disease process. Objective: To describe and analyze qualitative research on health issues published in Colombian journals between 2011 and 2021. Materials and methods: A descriptive study on qualitative health research published in Colombian journals between 2011 and 2021 was carried out. Results: Eighty-one articles were included. The journal with the highest number of publications was the Revista de Salud Pública (44.4%). The year with the highest production corresponded to 2019 and the main design was the fundamental theory (17.3%). In 79% of the articles, women were the main author and nursing was the most frequent profession of undergraduate training. The most frequent topic was HIV/AIDS (12.3%), followed by cancer (11.1%). In 24.6% of the studies, a software was used for the analysis. Conclusions: Qualitative research in public health has had a variable dynamic in scientific production between 2011 and 2021. Despite its benefits, the adoption of computer programs for qualitative analysis is rare. Nursing stands out as the area that concentrates the largest number of qualitative studies in public health with contributions on topics such as COVID-19 and HIV/AIDS.